Risk of zoonotic pathogen exposure among veterinary professionals and students at veterinary schools and best practices to minimize this risk on individual and institutional levels - Heinrich, Ellen R.E. (Kansas State University, 2014)
The College of Veterinary Medicine (CVM) environment is a place where veterinarians, veterinary staff, and veterinary students may have increased risk of exposure to zoonotic pathogens. This exposure may occur in classrooms or laboratories where pre-clinical veterinary students and non-clinical staff frequent. Exposure may also occur in the veterinary teaching hospital (VTH) and may impact veterinary patients, clinicians, interns, residents, veterinary technicians, veterinary students, animal caretakers, and others. This thesis is divided into 3 chapters. The first chapter describes a current review of the literature involving risk of zoonotic pathogen exposure at VTHs including descriptions of the most commonly documented zoonotic pathogens and their transmission, environmental sources of zoonotic pathogens at VTHs, and ways to prevent zoonotic pathogen exposure at individual and institutional levels. The second chapter describes an original research study of hand hygiene behavior among pre-clinical veterinary students at a CVM. The purpose of this study was to determine if a campaign could improve hand hygiene among veterinary students at extracurricular meetings serving meals. Campaign interventions included a 3.5 minute educational video and a novel motivational poster. The video was presented to all 1st, 2nd, and 3rd year veterinary students. Posters encouraging hand sanitization were displayed on doors and tables alongside sanitizers at each meeting. Observational hand hygiene data were collected immediately after introduction of interventions and again 3 months later. Environmental sampling for presence of bacteria in and around meeting locations was also performed. Observed hand hygiene was lowest during baseline (11.0% +/- 1.7), improved significantly post-intervention (48.8% +/- 3.2), and remained improved at 3-month follow-up (33.5% +/-4.0). Females had higher probability of hand- sanitizing (35.9% ± 2.2) than males (21.4% ± 2.4) (p<0.01). Clostridium perfringens was isolated from 2/42 samples, and Salmonella spp. were isolated from 4/42 samples. This study documented that a short-term public health campaign targeting veterinary students successfully improved hand hygiene before meals. The final chapter discusses future areas of research in the realm of risk of zoonotic pathogen exposure and risk mitigation at CVMs.
Keywords: Zoonotic pathogen exposure; Veterinary teaching hospital; Hand hygiene; Public health; College of Veterinary Medicine; Hand hygiene campaign; Public Health (0573); Veterinary Medicine (0778)